A sintaxe da violência entre Hegel e Marx The syntax of violence between Hegel and Marx - Vittorio Morfino (Trans/Form/Ação, 2008)
Trata-se de investigar a tese marxiana acerca do papel da violência na história, tal como enunciada em O Capital, analisando sua sintaxe de matriz hegeliana e o modo como Engels articula tal tese, para então defender uma interpretação não-teleológica da violência, segundo a qual esta apresenta uma pluralidade de formas, um caráter totalmente difuso e uma pesada materialidade. The Marxian Thesis about the role of violence in History, as it is enunciated in The Capital, is investigated through an analysis of the Hegelian character of its syntax, and the way Engels develops it; a non-teleological interpretation of the thesis is then defended, one that understands that violence presents a plurality of forms, a pervasive character and a heavy materiality.